Child Pain Intensity and Parental Attitudes toward Complementary and Alternative Medicine Predict Post-Tonsillectomy Analgesic Use - Jaclyn Lee; Katherine Delaney; Molly Napier; Elizabeth Card; Brittany Lipscomb; Jay Werkhaven; Amy S. Whigham; Andrew D. Franklin; Stephen Bruehl; Amanda L. Stone (MDPI AG, 2020)
Parental attitudes regarding pain interventions and perceptions of their child's pain intensity likely influence the decision to administer postoperative analgesics. Our study examined the impact of daily fluctuations in child pain intensity and parental attitudes regarding complementary and alternative medicine (CAM) on analgesic administration following pediatric tonsillectomy. Parents of children undergoing tonsillectomy (n = 33) completed a survey assessing CAM attitudes and a 7-day postoperative electronic daily diary to record their child's daily pain intensity and analgesic medications (acetaminophen, ibuprofen, or oxycodone). Generalized linear mixed models with Poisson distributions evaluated the effects of within-person (child's daily pain intensity) and between-person (average postoperative pain, parental CAM attitudes) components on the number of medication doses administered. Higher daily pain intensity was associated with more oxycodone doses administered on a given day, but not acetaminophen or ibuprofen. Positive parental CAM attitudes were associated with less oxycodone use, beyond the variations accounted for by the child's daily pain intensity and average postoperative pain. Both parental CAM attitudes and their child's daily pain intensity were independently associated with parental decisions to administer opioids following tonsillectomy. Understanding factors influencing individual variability in analgesic use could help optimize children's postoperative pain management.